1995
DOI: 10.1046/j.1471-4159.1995.65010149.x
|View full text |Cite
|
Sign up to set email alerts
|

The Second Messenger, Cyclic AMP, Is Not Sufficient for Myelin Gene Induction in the Peripheral Nervous System

Abstract: The adenylyl cyclase‐cyclic AMP (cAMP) second messenger pathway has been proposed to regulate myelin gene expression; however, a clear correlation between endogenous cAMP levels and myelin‐specific mRNA levels has never been demonstrated during the induction or maintenance of differentiation by the myelinating Schwann cell. Endogenous cAMP levels decreased to 8–10% of normal nerve by 3 days after crush or permanent transection injury of adult rat sciatic nerve. Whereas levels remained low after transection inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 44 publications
4
14
0
Order By: Relevance
“…This is evident by previous studies, which have shown that cAMP in rat sciatic nerve increases during nerve regeneration and decreases following nerve injury (Poduslo et al 1995; Walikonis et al 1998). Furthermore, it has been shown that there is a high endogenous cAMP level in myelinated nerve, but not in non-myelinated nerve, hence associating cAMP elevation with building of the myelin sheath (Poduslo et al 1995). Therefore, developmental regulation of endogenous cAMP might be associated with the cAMP-dependent axonal function that regulates postnatal development of myelinating Schwann cell lineage in the PNS.…”
Section: Discussionsupporting
confidence: 66%
“…This is evident by previous studies, which have shown that cAMP in rat sciatic nerve increases during nerve regeneration and decreases following nerve injury (Poduslo et al 1995; Walikonis et al 1998). Furthermore, it has been shown that there is a high endogenous cAMP level in myelinated nerve, but not in non-myelinated nerve, hence associating cAMP elevation with building of the myelin sheath (Poduslo et al 1995). Therefore, developmental regulation of endogenous cAMP might be associated with the cAMP-dependent axonal function that regulates postnatal development of myelinating Schwann cell lineage in the PNS.…”
Section: Discussionsupporting
confidence: 66%
“…However, more direct evidence was provided recently with the discovery of a novel G-protein-coupled receptor that is required for SC myelination in zebrafish and that it does so in a cAMP-dependent manner (47). We can therefore speculate that dedifferentiation and/or myelin loss may simply result from a reduction of cAMP in SCs, as those observed after injury (48). In support of this, we show that a reduction of intracellular cAMP is sufficient to trigger a dedifferentiating signal that directly impinges on the early transcriptional control of myelin gene expression.…”
Section: Discussionmentioning
confidence: 92%
“…However, the role of cAMP signaling in regulating the phenotype of Schwann cells is complex. Although forskolin can promote both proliferation and differentiation in cultured Schwann cells, in injured nerves, intracellular cAMP levels rise after reexpression of P0, and increasing the concentration of intracellular cAMP does not induce myelin gene expression (Poduslo et al, 1995). The identification of additional genes that are regulated by forskolin in Schwann cells would thus enhance our understanding of the functions of cAMP signaling in Schwann cell differentiation.…”
mentioning
confidence: 99%